PEMANFAATAN TEPUNG JAGUNG PADA PEMBUATAN SELAT GALANTIN SOLO JAGUNG (SELASOJA) - Endang Mulyatiningsih, Indri Setiani (Prosiding Pendidikan Teknik Boga Busana, 2020)
Corn flour is one of the results of cereal commodities, where production is very high in Indonesia. The use of corn flour for substitution in the manufacture of selat galantine solo aims to utilize local food sources and to introduce them to the wider community. The selat galantine solo is one of the typical foods originating from of Surakarta which is usually made of chopped and seasoned chicken and added bread crumb and the egg is then wrapped like rice cake then steamed, serving usually with vegetables such as green beans, potatoes, carrots. The purpose of this study was to find a new formula, find out the community’s acceptability, and find out the nutritional value information for the innovation product of selat galantin solo jagung. This study uses the Research and Development method with a 4-D model (define, design, develop, and dissemination). The tests used included validation test I, validation test II, limited scale sensory test, and wide-scale sensory test (exhibition) in which the panelists consisted of semi-trained and untrained. The results of this study are to find the best formula from the substitution of corn flour, which is equal to 40%, the community can accept and really like the same product. Keywords: corn flour, substitution, selat galantine solo